O ensino por investigação criando possibilidades para os professores de ciências e biologia em formação inicial a partir da pesquisa-ação - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
Resumo em língua estrangeira: Thus, the present research aimed to contribute to the initial training of science teachers in the use of the inquiry-based teaching approach, with a view to overcoming difficulties and making changes in pedagogical practice. To do so, the research was carried out in line with the principles of the qualitative approach and action research with students from the Biological Sciences undergraduate course, during the 5th and 6th semesters, at UEG, Câmpus Central - Headquarters, in Anápolis, Goiás. The research was conducted in two moments: the first, with observations of the participants, during the discipline of Orientation and Practice of Science Teaching, application of questionnaires, semi-structured interviews; in the second moment, an intervention was conducted with these students, characterized by a remote training, with proposals for readings, studies and activities that would provide knowledge of the principles of teaching by research and stimulate a reflective and motivating practice. During the research it was possible to verify difficulties and gaps in the initial training and the insecurity of future teachers in their teaching practice, characterized by being traditional and a transmitter of concepts. During the training, weaknesses in the theoretical basis, resistance to the use of the approach, difficulties in planning activities, and a lack of experience were noticed. We highlight the potential of the inquiry-based teaching approach, which enables the development of autonomous, mediator, and reflective teachers who are able to teach science in a contextualized and interactive way, to develop activities that promote the engagement of their students and lead them to the development of scientific culture. Thus, I consider that the investigative approach should be intermingled with the subjects offered in undergraduate courses, as a way to allow students to be trained as active professionals, capable of building their knowledge and who know how to mediate the paths in the teaching and learning process.
Inquiry-based teaching creating possibilities for science and biology teachers in initial training through action research
Keywords: Ensino por investigação; Formação inicial de professores; Ensino de Ciências; Teaching through research; Initial teacher education; Science education; EDUCACAO::ENSINO-APRENDIZAGEM; ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO